Koloni Lebah Madu (Apis cerana F.) Sebagai Agen Penyerbuk Pada Tumbuhan Terung Ungu (Solanum melongena L.) Pada Sistem Pertanian Lokal Bali - I Gusti Ayu Putu Intan Udayani; Ni Luh Watiniasih; I Ketut Ginantra (Prodi Magister Ilmu Biologi, Fakultas MIPA, Universitas Udayana, 2020)
Pollination is the most important live processes for plant especially for seedling plant. Some previous research results show that insects play an important role in helping the pollination process both in wild plants and in productive plants. The eggplant (Solanum melongena L.) is one of the important agricultural commodities. However, the eggplant production in the local farming system today often experiences obstacles when its production is not in sufficient quantities. The potential of Apis cerana L. as a pollinator is a chance solve the productions problems. The purpose of this study was to determine the role of honey bees (Apis cerana L.) in increasing yield of eggplant (Solanum melongena L.).This study obtained the eggplant productivity data. All data was collected and analyzed with SPSS 17 statistical program. Before analysis, all data normality were tested and it was analyzed by One-way ANOVA and when significant differences were found, analysis was continued with the Tuckey Test to find out the difference within treatment with a significance value ???? <0.05 .The results of this study note that bees have a certain amount of time to carry out their activities and the addition of bees colony to the experimental field produced two times more of yield compared with the other groups that were not treated with he colony. Keyword: Apis cerana, Solanum melongena, crop plant productivity